Just how good is unemployment as a measure of welfare? a note - De Dios, Emmanuel; Dinglasan, Katrina (The Philippine Review of Economics, 2015)
Governments are rightly concerned with employment generation to make growth inclusive. The use of the open unemployment rate to measure success, however, may be misplaced. In a developing country like the Philippines, with a large informal sector and in the absence of unemployment insurance, open unemployment is primarily a middle-class phenomenon: the unemployed are not predominantly poor, and the poor are not predominantly unemployed. Measures of productivity and shifts of labor across sectors may contain more information and be more welfare-relevant.